2011
DOI: 10.4236/pp.2011.21004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Pharmacokinetics of Oral Drugs

Abstract: Establishment of rational dosage regimens requires the knowledge of pharmacokinetics and pharmacodynamics in the target population. It has been established that side effects produced by drugs are more frequent in women than in men. This may be due to two possibilities, one is that normalized dose received by women is higher than men and the other is that anatomical and physiological characteristics are a quite different. In this review, some aspects that may play a role in the generation of such differences ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…The matching procedure in the present study together with the exclusion of multiple determinations was important to make the groups comparable but, inevitably, resulted in a considerable decrease of sample size. 24,25 Although switch studies suggest differences between brand-name and generic versions of psychotropic drugs regarding efficacy or adverse events 7,12-15 and although variation of bioequivalence of the same compound in dependence of the respective manufacturer is a long-known problem, 26 there still is a lack of studies comparing different generics with brand-name medication, which would involve higher number of patients under steady state conditions. This might be one reason for the lack of any difference in VEN, ODV, and VEN + ODV serum concentrations between brand-name and generic formulations in contrast to the study of Chenu et al 8 The different pattern of influence of gender, age, and smoking habits on serum concentrations in generic and brand-name VEN corresponds with unequivocal results regarding these variables in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The matching procedure in the present study together with the exclusion of multiple determinations was important to make the groups comparable but, inevitably, resulted in a considerable decrease of sample size. 24,25 Although switch studies suggest differences between brand-name and generic versions of psychotropic drugs regarding efficacy or adverse events 7,12-15 and although variation of bioequivalence of the same compound in dependence of the respective manufacturer is a long-known problem, 26 there still is a lack of studies comparing different generics with brand-name medication, which would involve higher number of patients under steady state conditions. This might be one reason for the lack of any difference in VEN, ODV, and VEN + ODV serum concentrations between brand-name and generic formulations in contrast to the study of Chenu et al 8 The different pattern of influence of gender, age, and smoking habits on serum concentrations in generic and brand-name VEN corresponds with unequivocal results regarding these variables in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, these physiological differences drive the rate and extent of absorption from the gastrointestinal tract. Further sex differences are observed in transport protein expression due to regulation by sex hormones [72,83,60]. Similarly, the extent of plasma protein binding is also affected by sex hormones, driving wider distributions in female patient responses during menses [72,79,73].…”
Section: Model Parameterization For Special Populationsmentioning
confidence: 99%
“…For example, P-glycoprotein (P-gp) is a plasma membrane-bound transporter, which is present in drug-eliminating organs, mainly the liver and to a lesser extent in the intestine [85,87]. Many drugs are substrates to P-gp and thus an important consideration for drug product development is understanding its influence on bioavailability [60,88,85]. This protein has higher expression in males [72,83,60].…”
Section: Model Parameterization For Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature evaluating gender differences based on the BE data submitted to the USFDA suggested that, in the studies that were not adjusted to the body weight, 20%–88% higher AUC values in females were observed (Chen et al., 2000). Generally females have a higher body fat percentage, smaller plasma volume, and lower organ blood flow than the males (Carrasco‐Portugal & Flores‐Murrieta, 2011). The influence of body fat on the distribution of lipophilic drugs is evident from the higher volume of distribution for diazepam (Ochs et al., 1981).…”
Section: Introductionmentioning
confidence: 99%